1998
DOI: 10.1093/rheumatology/37.6.691
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sjogren's-like syndrome in a cohort of HIV-1-positive patients: descriptive pathology and immunopathology

Abstract: The aims of the study were (a) to investigate the prevalence of Sjögren's-like syndrome (SLS) in an unselected population of HIV-1-positive patients and (b) to describe the pathology and immunopathology of the labial minor salivary gland biopsy. Seventy-seven HIV-1-positive patients were asked to answer the validated questionnaire of the European preliminary criteria for the classification of Sjögren's syndrome on oral and ocular sicca symptoms. Twenty-six patients gave one positive answer to both ocular and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
7

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 0 publications
0
41
0
7
Order By: Relevance
“…In contrast, data from a labial gland biopsy-based study of 30 unselected treatment-naive HIV-1-positive patients in West Africa estimated the prevalence of SS to be 48% [34]. Clinically, Kordossis et al [32] found a great similarity in the clinical expression of DILS and primary SS and suggested that DILS should be considered as a "possible" SS. Although they seem to differ in certain aspects, HIV-related sicca syndrome generally resembles SS, and the idea that DILS should be considered as a viral-related sicca syndrome (similar to that described in HCV patients) rather than a separate disorder seems to be more appropriate.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, data from a labial gland biopsy-based study of 30 unselected treatment-naive HIV-1-positive patients in West Africa estimated the prevalence of SS to be 48% [34]. Clinically, Kordossis et al [32] found a great similarity in the clinical expression of DILS and primary SS and suggested that DILS should be considered as a "possible" SS. Although they seem to differ in certain aspects, HIV-related sicca syndrome generally resembles SS, and the idea that DILS should be considered as a viral-related sicca syndrome (similar to that described in HCV patients) rather than a separate disorder seems to be more appropriate.…”
Section: Human Immunodeficiency Virusmentioning
confidence: 97%
“…On the one hand, the predominance of CD8 lymphocytes in the salivary glands of HIV patients is not surprising because of the specific destruction of CD4 cells by the virus. On the other hand, neither is the low In 1998, Kordosis et al [32] described an 8% prevalence of HIV-related sicca syndrome in Greek HIV-1 positive patients. In a similar study, conducted in a larger HIV cohort in the USA, a prevalence of 3% was found on the basis of a different methodology [33].…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…On the other hand, it differs by the high frequency of extra glandular sites of lymphocytic infiltration, such as lungs, muscles and liver, scarcity or absence of serum autoantibodies and the nature of infiltrating lymphocytes. While in Sjögren syndrome presents lymphocytic infiltration of CD4+ and in DILS it is a CD8+ lymphocytes and anti-Ro and anti-La are seen less frequently (2,31) . The prevalence of DILS had dropped significantly after the introduction of HAART, indirectly inferring that the HIV infection contributes to DILS pathogenesis.…”
Section: Hivmentioning
confidence: 99%
“…A prevalência do olho seco em pacientes infectados pelo HIV em estudos prévios variou de 7,79% a 38,8% e a sintomatologia do olho seco tem um impacto relevante na qualidade de vida destes pacientes (20)(21)(22)(23)(24) . O presente estudo avaliou 20 pacientes portadores do vírus HIV com diagnóstico de olho seco e comparou a eficácia do tratamento com suplementação lacrimal (carboximetilcelulose sódica 0,5%) ou com suplementação lacrimal associada à terapia anti-inflamatória (carboximetilcelulose sódica 0,5% e ciclosporina 0,05%).…”
Section: Introductionunclassified